Congenital Bullous Syphilis: A Case Report from Italy and a Comprehensive Literature Review - Edoardo Cammarata; Elia Esposto; Nunzia Di Cristo; Chiara Airoldi; Elena Bernascone; Valentina Burzio; Paola Savoia (Medicina)
Background and Objectives: Congenital syphilis remains a significant global health concern, with severe morbidity and mortality if undiagnosed and untreated. Although many infants appear asymptomatic at birth, subtle clinical signs—including bullous lesions (congenital bullous syphilis, also known as pemphigus syphiliticus)—may facilitate early detection. Recognizing this rare manifestation is crucial for timely intervention, reducing serious outcomes. Materials and Methods: We systematically reviewed Medline (PubMed), Embase, and the Cochrane Central Register of Controlled Trials from inception to December 2024 for cases of congenital bullous syphilis, also known as pemphigus syphiliticus. We extracted demographic, clinical, laboratory, radiological, treatment, and outcome data. Additionally, we included clinical information from a newly documented case of congenital bullous syphilis managed in our center. Results: Twenty-four cases of congenital syphilis with bullous lesions were identified, twenty with sufficient detail for analysis. Patients presented three distinct clinical patterns: confined palmoplantar lesions, acrally distributed lesions, and diffuse bullous-erosive involvement. Despite variable severity, cutaneous manifestations provided a key diagnostic clue. Nontreponemal and treponemal serologic tests were central to diagnosis, supported by maternal screening and imaging. Intravenous penicillin G was the most frequently employed therapy. While most infants achieved remission, severe respiratory involvement was associated with mortality. Our new case aligned with these findings, demonstrating full resolution after appropriate antibiotic therapy. Conclusions: Bullous syphilis, though rare, is an important early sign of congenital syphilis. Prompt recognition and diagnosis—enabled by diligent maternal screening, targeted neonatal testing, and careful clinical examination—are essential to initiate timely penicillin therapy and prevent severe complications or death. This review underscores the need for heightened clinical vigilance and adherence to established guidelines for syphilis screening and treatment during pregnancy, ultimately improving neonatal outcomes.